Pulmonary vein isolation‐induced vagal nerve injury and gastric motility disorders detected by electrogastrography: The side effects of pulmonary vein isolation in atrial fibrillation (SEPIA) study. (19th January 2023) - Grosse Meininghaus, Dirk; Freund, Robert; Kleemann, Tobias; Geller, Johann Christoph; Matthes, Harald
Abstract: Introduction: Safety of pulmonary vein isolation (PVI) has been established in clinical studies. However, despite prevention efforts the incidence of damage to (peri)‐esophageal tissue has not decreased, and the pathophysiology is incompletely understood. Damage to vagal nerve branches may be involved in lesion progression to atrio‐esophageal fistula. Using electrogastrography, we assessed the incidence of periesophageal vagal nerve injury (VNI) following atrial fibrillation ablation and its association with procedural parameters and endoscopic results. Methods: Patients were studied using electrogastrography, endoscopy, and endoscopic ultrasound before and after cryoballoon (CB) or radiofrequency (RF) PVI. The incidence of ablation‐induced neuropathic pattern (indicating VNI) in pre‐ and postprocedural electrogastrography was assessed and correlated with endoscopic results and ablation data. Results: Between February 2021 und January 2022, 85 patients (67 ± 10 years, 53% male) were included, 33 were treated with CB and 52 with RF (38 with moderate power moderate duration [25–30 W] and 14 with high power short duration [50 W]). Ablation‐induced VNI was detected in 27/85 patients independent of the energy form. Patients with VNI more frequently had postprocedural endoscopically detected pathology (8% mucosal esophageal lesions, 36% periesophageal edema, 33% food retention) but there was incomplete overlap. Pre‐existing esophagitis increased the likelihood of VNI. Ablation data and esophageal temperature data did not predict VNI. Conclusion: PVI‐induced VNI is quite common and independent of ablation energy source. VNI is part of (peri)‐esophageal damage and only partially overlaps with endoscopic findings. VNI‐associated acidic reflux may be involved in the complex pathophysiology of esophageal lesion progression to fistula.